The medial and lateral epicondyle as a reliable landmark for intra-operative joint line determination in revision knee arthroplasty. Issue 7 (July 2016) - Ozkurt, B.; Sen, T.; Cankaya, D.; Kendir, S.; Basarır, K.; Tabak, Y.
Abstract : Objectives: The purpose of this study was to develop an accurate, reliable and easily applicable method for determining the anatomical location of the joint line during revision knee arthroplasty. Methods: The transepicondylar width (TEW), the perpendicular distance between the medial and lateral epicondyles and the distal articular surfaces (DMAD, DLAD) and the distance between the medial and lateral epicondyles and the posterior articular surfaces (PMAD, DLAD) were measured in 40 knees from 20 formalin-fixed adult cadavers (11 male and nine female; mean age at death 56.9 years, sd 9.4; 34 to 69). The ratios of the DMAD, PMAD, DLAD and PLAD to TEW were calculated. Results: The mean TEW, DMAD, PMAD, DLAD and PLAD were 82.76 mm (standard deviation (sd ) 7.74), 28.95 mm (sd 3.3), 28.57 mm (sd 3), 23.97 mm (sd 3.27) and 24.42 mm (sd 3.14), respectively. The ratios between the TEW and the articular distances (DMAD/TEW, DLAD/TEW, PMAD/TEW and PLAD/TEW) were calculated and their means were 0.35 (sd 0.02), 0.34 (sd 0.02), 0.28 (sd 0.03) and 0.29 (sd 0.03), respectively. Conclusion: This method provides a simple, reproducible and reliable technique enabling accurate anatomical joint line restoration during revision total knee arthroplasty. Cite this article: B. Ozkurt, T. Sen, D. Cankaya, S. Kendir, K. Basarır, Y. Tabak. The medial and lateral epicondyle as a reliable landmark for intra-operative joint line determination in revision knee arthroplasty. Bone Joint Res 2016;5:280–286. DOI: 10.1302/2046-3758.57.BJR-2016-0002.R1.